Computational analysis to investigate the anti-rheumatic potential of plant-based small molecule inhibitor targeting tumor necrosis factor α - Rehman, Sanaya; Bhatti, Attya; John, Peter (Frontiers in Pharmacology, 2023)
Objective This study aimed to assess the anti-rheumatic potential of Dodonaea viscosa and evaluate its bioactive small molecules for their beneficial effects in the management of rheumatoid arthritis. Methods In-vitro bioactivity assays were performed to assess the healing potential of D. viscosa, and the values were calculated by using the linear regression technique. In silico analysis was performed to identify the key inhibitors of the disease that target TNF-α. The plant extract was prepared using ethanol as a solvent via the Soxhlet method. Phytochemical and bioactivity testing was performed. Gas chromatography–mass spectrometry (GC–MS) analysis was conducted for bioactive plant compounds. A disease-specific target was shortlisted by HUB gene analysis. Molecular docking and molecular dynamics simulations were run for validation of the results. Results Phytochemical studies verified the presence of phenols, flavonoids, steroids, sterols, saponins, coumarins, tannins, and terpenoids. whereas the significant antioxidant and anti-inflammatory potential of plant extracts was evaluated by the DPPH and protein denaturation assays, respectively. In silico studies revealed that nine of the 480 compounds found in D. viscosa (ethanol extract) had drug-like properties. TNF- was identified as a key gene by HUB gene analysis. The results of molecular docking and MD simulation analysis revealed that 4-(1-Hydroxy-3-oxo-1H-isoindol-2-yl) benzoic acid (PubChemID 18873897) had the highest TNF-binding affinity. Conclusion 4-(1-Hydroxy-3-oxo-1H-isoindol-2-yl) benzoic acid (PubChemID 18873897) has the potential to be an effective small molecule TNF-inhibitor in the treatment of rheumatoid arthritis.